Effect of Leuhang Therapy on Lung Histopathology, Leukocytes, and Bronchoalveolar Lavage Fluid (BALF) in Asthma Rat Model - Imanulhaq, Hasbi; Septiani, Tria; Parwoko, Nasywa Asy Syaffa'; Ramadhan, Harry Rachman; Laksono, Bambang Tri (Journal of Experimental and Clinical Pharmacy (JECP), 2025)
The prevalence of asthma is increasing, especially in developing countries due to lifestyle and air pollution. In addition, asthma medications can cause serious side effects, such as the use of the asthma medication LABA, which causes the side effects of tachycardia, tremor, and epicardial elevation, which is considered quite dangerous for the elderly. Sundanese people from West Java have a traditional therapy called Leuhang therapy. This therapy is believed to have various properties, including anti-asthma. In addition, this therapy is also safer and has minimal side effects. This study aims to obtain an optimal Leuhang therapy formula for preventing asthma recurrence and determine the relationship between plant extract vapor in Leuhang and its effects on the organs of asthma-induced mice. The study was conducted by dividing the mice into several groups, namely normal control, positive control, comparison, test I, and test II. Each mouse was given treatment according to its respective group. Based on the results obtained from this study, leuhang therapy with a combination of formulas focusing on anti-asthmatic properties showed anti-asthmatic activity against OVA-induced allergic asthma. The combination treatment decreased the total and differential cell counts in blood and BALF and affected the thickness of mouse lung mucosa and muscle, thus demonstrating its anti-inflammatory properties. Leuhang therapy also reduced the infiltration of neutrophils, lymphocytes, and plasma, showing its immunomodulatory properties. Statistical tests using One-Way ANOVA showed a p-value of <0.05, meaning that the four groups' mean lung histopathology scores were significantly different. Thus, Leuhang therapy has been shown to have promising potential in the alternative treatment of asthma.